Impact of multi-modal web-based rehabilitation on occupational performance and upper limb outcomes: Pilot randomized trial in children with acquired brain injuries - Sakzewski, L.; Lewis, M.; Mckinlay, L.; Ziviani, J.; Boyd, Roslyn (Wiley-Blackwell Publishing Ltd., 2016)
Aims: To determine whether the multi-modal web-based rehabilitation 'Move it to improve it' (Mitii) is more effective than wait list control (usual care) to improve occupational performance, upper limb function, and visual perception in children with acquired brain injury (ABI). Method: Fifty-eight randomly allocated children (53% males; mean age 11y 11mo, SD 2y 6mo; Manual Abilities Classification Scale equivalent I=32, II=24, III=2; mean Full-scale IQ 75.8, SD 16.2) received either 20 weeks of Mitii (n=29) or usual care (n=29). Mitii comprised upper limb, cognitive, visual perception, and gross motor tasks, recommended for 30 minutes per day, 6 days per week, over 20 weeks. Outcomes were the Assessment of Motor and Process Skills (AMPS), Melbourne Assessment of Unilateral Upper Limb Function, Jebsen-Taylor Test of Hand Function, Test of Visual Perceptual Skills, Assisting Hand Assessment (AHA), and Canadian Occupational Performance Measure. The primary comparison at 20 weeks between groups on the AMPS process and motor measures used generalized estimating equations. Results: Groups were equivalent at baseline. Participants completed on average 17.6 hours (range 0-46h) of Mitii. There were no differences between groups on the primary outcome (AMPS process: estimated mean difference -0.1, 95% CI -0.3 to 0.2, p=0.589; and AMPS motor: estimated mean difference 0.2, 95% CI -0.1 to 0.5, p=0.192). There were no differences between groups on overall visual perception, upper limb, and occupational performance outcomes. Interpretation: Mitii led to negligible changes on all primary and secondary outcomes compared with usual care. This likely reflects the small dose achieved and poses questions around the acceptability and feasibility of home-delivered Mitii in this population of children with ABI.